An Experimental Study of Structural Identification of Bridges Using the Kinetic Energy Optimization Technique and the Direct Matrix Updating Method - Gwanghee Heo; Joonryong Jeon (Shock and Vibration)
This paper aims to develop an SI (structural identification) technique using the KEOT and the DMUM to decide on optimal location of sensors and to update FE model, respectively, which ultimately contributes to a composition of more effective SHM. Owing to the characteristic structural flexing behavior of cable bridges (e.g., cable-stayed bridges and suspension bridges), which makes them vulnerable to any vibration, systematic and continuous structural health monitoring (SHM) is pivotal for them. Since it is necessary to select optimal measurement locations with the fewest possible measurements and also to accurately assess the structural state of a bridge for the development of an effective SHM, an SI technique is as much important to accurately determine the modal parameters of the current structure based on the data optimally obtained. In this study, the kinetic energy optimization technique (KEOT) was utilized to determine the optimal measurement locations, while the direct matrix updating method (DMUM) was utilized for FE model updating. As a result of experiment, the required number of measurement locations derived from KEOT based on the target mode was reduced by approximately 80% compared to the initial number of measurement locations. Moreover, compared to the eigenvalue of the modal experiment, an improved FE model with a margin of error of less than 1% was derived from DMUM. Thus, the SI technique for cable-stayed bridges proposed in this study, which utilizes both KEOT and DMUM, is proven effective in minimizing the number of sensors while accurately determining the structural dynamic characteristics.